PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, DAN UKURAN PERUSAHAAN PADA KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR - Devi, Ni Putu Yunita; Erawati, Ni Made Adi (E-Jurnal Akuntansi, 2014)
This study aims to determine the effect of managerial ownership, leverage, and firm size on dividend policy. The population in this study were 450 companies listed in Indonesia Stock Exchange. The data used is in the form of quantitative secondary data derived from the financial statements of companies listed on the Indonesia Stock Exchange in 2010-2012. Based on the results of data analysis using multiple linear regression, shows that managerial ownership has no effect on dividend policy, leverage negatively affect dividend policy and firm size has a positive effect on dividend policy .
Keywords: managerial ownership, leverage, and dividend